A Novel Broker-Based Hierarchical Authentication Scheme in Proxy Mobile IPv6 Networks - Jang, Su-Hwan; Jeong, Jongpil; Park, Byungjun (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2018: Anais do XXX International Symposium on Computer Architecture and High Performance Computing, 2018)
Most of the current research about Proxy Mobile IPv6 (PMIPv6) focuses on how to optimize the interactive processes between the PMIPv6 and AAA (Authentication, Authorization, and Accounting) protocol. This paper describes a cost-effective hierarchical authentication scheme, which makes its focus on minimizing the authentication latency in AAA processing. In this scheme, a hierarchical AAA architecture is proposed, in which the AAA servers are deployed on the Local Mobility Anchor (LMA), the Root AAA server manages several Leaf AAA servers and the Brokers on behalf of the AAA server in home domain. The simulation results shows that the proposed scheme reduces the handoff and authentication latency evidently compared to the previous traditional authentication combination modeling.